Authority Relations in Different Organizational Systems - Limerick, David C. (Academy of Management Review, 1976)
Reactions of organizational participants to authority relations can be understood by examining the total organizational system in which authority relations are embedded. Differences in such relations, and reactions to them, are examined within the framework of a matrix of organizational systems based on different assumptions about both people and organizations.